Перспективы автоматизации процессов библиографического труда - Владимировас, Левас (Knygotyra, 1981)
The automation of the bibliographic processes is one of the most urgent problems we have to face and to solve in the nearest future. The information explosion and the immense holdings of the libraries require a new technology to handle the float of information and printed matter. In the paper the possibilities and prospects of using computer for the above purpuse are analysed. Some foreign experience in using computer in improving bibliographic access and assisting the library user to obtain information are described. (MARC, MEDLARS and other projects). The first successful Soviet experiments to computerise the bibliographic processes are discusses. Particularely the experience in this field of the Allunion book chamber and of the Public Library for Science and Technology (Moscow). The first experiments in Lithuania in application of computer to handle the bibliographic data are described. As main and requisite condition for further progress in this field, besides the necessary computer “hard — and software”, the training of library personnel to handle the new technology is brought forward.